Current Practices and Challenges in Menstrual Hygiene Management (A Case Study of Birenranagar, Surkhet) - Adhikari, Khagendra Prasad (NPRC Journal of Multidisciplinary Research, 2025)
This study explores the status of menstrual hygiene practices and challenges among flood-affected communities in Girighat, Surkhet, Nepal, where menstruation remains shrouded in stigma due to cultural taboos, limited education, and inadequate access to sanitary products. Using a descriptive research design and purposive sampling, the study assessed the knowledge, perceptions, and practices of 103 women, examining socio-demographic factors, cultural restrictions, and resource accessibility. Findings reveal that while most respondents recognized public awareness as crucial for improving menstrual hygiene, significant barriers persist, including insufficient government coordination, weak institutional frameworks, and lack of proper monitoring. The study underscores the urgent need for better access to menstrual products, targeted education programs, and community-based initiatives to dismantle harmful cultural norms. Additionally, it highlights the importance of multi-sectoral collaboration involving government bodies, NGOs, and international organizations to enhance menstrual health management. Addressing these challenges can significantly improve health outcomes, dignity, and educational opportunities for women in rural Nepal, calling for stronger policy implementation and grassroots engagement in Girighat and similar marginalized regions.